2022
DOI: 10.1186/s12884-022-04833-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of elective and emergency caesarean delivery among reproductive-aged women in Bangladesh: evidence from demographic and health survey, 2017–18

Abstract: Background Over the years, an increasing trend of unnecessary caesarean section (c-section) deliveries has raised concerns in Bangladesh. So far, many studies have reported the risk factors of c-section delivery in Bangladesh. However, most of these studies did not estimate the predictors of the two c-section procedures (i.e., emergency and elective) separately based on the timing of the c-section decision. This study solely brings forward the role of socio-demographic and economic factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…The study findings showed that mothers who were 30 years and above were more than twice likely to choose elective CS. This study findings correspond with similar studies conducted (13,41,43,45). Older mothers may choose elective CS because of their previous experience with childbirth, particularly through vaginal delivery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study findings showed that mothers who were 30 years and above were more than twice likely to choose elective CS. This study findings correspond with similar studies conducted (13,41,43,45). Older mothers may choose elective CS because of their previous experience with childbirth, particularly through vaginal delivery.…”
Section: Discussionsupporting
confidence: 93%
“…To have valid and reliable predictors of elective CS, compared to other similar studies (41,43,45), this study used backward stepwise regression to select most influential predictors of elective CS in Rwanda. By eliminating the unnecessary predictors of elective CS in this current study, the model is easier to understand and interpret, particularly as the study findings could influence decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a high level of education improves access to healthcare services, where good pregnancy surveillance prevents complications that lead to CD, in particular emergencies. According to the present study findings, women from wealthy families were more likely to have CD than those from low-income families, and this is consistent with previous research [10,12,15,37]. Various studies have suggested that financial constraints in the developing world contribute to the unavailability of many healthcare interventions, including CD [38].…”
Section: Discussionsupporting
confidence: 92%
“…Women who opt for CSMR should be delivered no earlier than 39 weeks of gestation unless there are other clinical indications. It is crucial for women to be well informed about the risks of placenta praevia, placenta accreta spectrum, intrauterine mortality and caesarean hysterectomy in subsequent pregnancies [4]. Therefore, it is essential to provide these women with adequate knowledge before they can make significant decisions and exercise their autonomy competently as patients.…”
Section: Indications and Recommendationsmentioning
confidence: 99%
“…A planned or elective caesarean section is performed before the onset of labour. Contrarily, an emergency C-section is a procedure performed before or during labour out of concern for the mother or the foetus [4].…”
Section: Introductionmentioning
confidence: 99%